Pengaruh Rentabilitas dan Ukuran Perusahaan terhadap Return Saham dengan Kebijakan Dividen sebagai Variabel Moderating - Teguh Erawati; Anita Primastiwi; Muhammad Hafizh Ilham (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
The purpose of this study was to examine the effect of profitability and firm size on stock returns with dividend policy as a moderating variable. This study uses a sample of food and beverage companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2019 period. The sampling method in this study used purposive sampling. The number of samples in this study were 12 companies. Hypothesis testing in this study used multiple linear regression methods and moderated regression analysis. The results of this study indicate that profitability is proxied to ROA and firm size has no effect on stock returns. Dividend policy is not able to moderate profitability as a proxy for ROA and firm size on stock returns. The coefficient of determination (R2) is known to be 0.48 or equal to 48%. This means that the Dividend Pay Ratio moderates the effect of Return on Assets by 48% on Stock Return, while the remaining 52% is influenced by other variables outside of this study. Keywords: profitability, return on assets, size and, dividend pay ratio